Data Transmission Using a Directly Modulated Widely Tunable DBR Laser With an Integrated Ti Thin Film Heater - Xiao Xie; Yunlong Liu; Qiang Tang; Lichen Zhang; Lingjuan Zhao; Hongliang Zhu; Wei Wang; Song Liang (IEEE Photonics Journal)
We present data transmission using a directly modulated distributed Bragg reflector (DBR) laser having an integrated Ti thin film heater in the DBR section and butt-jointed InGaAsP as DBR material. By combining DBR current tuning and thermal tuning effects, an over 16 nm wavelength tuning range is obtained. 5 Gb/s data transmissions are conducted at up to 25 km distance and different wavelengths. In the fabricated device, the butt-jointed InGaAsP material is also used for the formation of an integrated photodiode for monitoring the light power of the device.